PENERAPAN METODE RULE BASED REASONING DALAM SISTEM PAKAR DETEKSI DINI GANGGUAN KESEHATAN MENTAL PADA MAHASISWA - Wahyuni, Dita; Winarso, Doni (Department of Information System Muhammadiyah University of Riau, 2022)
College students are a special group who are going through a critical transition period from adolescence to adulthood and are trying to adjust, maintain good grades, plan for the future, and be away from home, so they are at risk of developing Mental Emotional Disorders (GME) such as depression, anxiety, and other psychiatric comorbidities. Based on this, college students who feel indications of mental problems should immediately talk to a psychologist. But in general, the difficulties faced by college students when conducting consultations, for example, the lack of mental health facilities in their environment or on their campus, shy to do the consultation, and the consultation fees. Based on these problems, an early detection process using an expert system is needed to assist college students in recognizing their mental health disorders. The Rule-Based Reasoning method focuses on expert rules that are entered into the system. Based on expert system testing using the Rule-Based Reasoning method on 10 experimental cases, almost all system results are in accordance with the detection made by the expert. Based on this, it is hoped that this system will help detect mental health disorders experienced by college students.